Antipsychotic Polypharmacy in Inpatients with Schizophrenia in Asia (2001−2009) - Xiang, Y.-T.; Wang, C.-Y.; Si, T.-M.; Lee, E.H. M.; He, Y.-L.; Ungvari, G. S.; Chiu, H.F. K.; Yang, S.-Y.; Chong, M.-Y.; Tan, C.-H.; Kua, E.-H.; Fujii, S.; Sim, K.; Yong, K. H.; Trivedi, J. K.; Chung, E.-K.; Udomratn, P.; Chee, K.-Y.; Sartorius, N.; Shinfuku, N. (Pharmacopsychiatry, 2012)
This study aimed to identify trends in the use of antipsychotic polypharmacy (APP) and their demographic and clinical correlates in the treatment of schizophrenia in Asia between 2001 and 2009.A total of 6761 schizophrenia inpatients in 9 Asian countries and territories were examined; 2399 in 2001, 2136 in 2004, and 2226 in 2009. Patients’ socio-demographic and clinical characteristics and prescriptions of psychotropic drugs were recorded using a standardized protocol and data collection procedure.The proportion of APP prescription decreased from 46.8% in 2001, to 38.3% in 2004, and increased to 43.4% in 2009, with wide inter-country variations at each survey. Multiple logistic regression analysis of the whole sample revealed that patients on APP were younger, had a higher dose of antipsychotics in chlorpromazine equivalents, and more severe positive and negative symptoms. They were also more likely to receive depot and first-generation antipsychotic drugs.The frequency of APP prescription varied between countries and territories, suggesting that a host of clinical and socio-cultural factors played a role in determining APP use in Asia. To resolve the discrepancy between treatment recommendation and clinical practice, regular reviews of prescription patterns are needed.
Keywords: schizophrenia; prescription patterns; antipsychotic polypharmacy